PENGARUH RELATIONSHIP MARKETING DAN BRAND TRUST TERHADAP LOYALITAS PELANGGAN (Survey Pelanggan Pada KFC Sudirman Cabang Pekanbaru) - Yudi Pratama C; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine how much influence relationship marketing and brand trust to consumer loyality. Samples in this study were taken as many as 100 respondents and techniques used Accidental Sampling approach. The data used in this study using primary data obtained from the answers of the respondents who had buyed in KFC Sudirman Pekanbaru branch. The method of analysis used in this study using multiple linear regression analysis consisting of the t test, F test, determination test and multiple linear regression equation. The results of this study show that Relationship marketing has a positive and significant impact on Consumer Loyality. Brand Trust has a positive and significant impact on Consumer Loyality. And then simultaneously relationship marketing and brand trust have a positive and significant impact on Consumer Loyality. There is an influence on the determination test of 57,8% which affects Consumer Loyality is explained by the variable relationship marketing and brand trust, while the remaining 42,2% is influenced by other variables and are not included in the regression analysis.Keywords: Relationship Marketing, Brand Trust, and Consumer Loyality